Screening for Latent Tuberculosis in Children With Immune-mediated Inflammatory Diseases Treated With Anti-tumor Necrosis Factor Therapy: Comparison of Tuberculin Skin and T-SPOT Tuberculosis Tests - Saniye GİRİT and Ayşe AYZIT ATABEK and Ebru ŞENOL and Tuba KOÇKAR KIZILIRMAK and Sevgi PEKCAN and Şafak GÖKTAŞ and Sedat ÖKTEM and Özgür KASAPÇOPUR and Haluk ÇOKUĞRAŞ (Archives of Rheumatology, 2020)
Objectives: This study aims to analyze the coherence between T-SPOT tuberculosis test (T-SPOT.TB) and tuberculin skin test (TST) with different cut-off values in screening latent tuberculosis infection (LTBI) both prior to and at the sixth month of anti-tumor necrosis factor (anti-TNF) treatment. Patients and methods: This prospective multicentric study included 57 children (34 girls, 23 boys, mean age 12.4±3.9 years; range, 6 to 18 years) diagnosed with immune-mediated inflammatory diseases (IMIDs) evaluated with TST and T-SPOT.TB for screening LTBI both prior to and at the sixth month of treatment with anti-TNF agents. Coherence between two tests was analyzed for TST cut-off values suggested by the local guidelines and also for different possible cut-off values of TST. Results: Tuberculin skin test was positive (≥5 mm) in 28.1% (n=16) of patients in the screening prior to treatment and in 33.3% (n=19) at the sixth month of treatment. T-SPOT.TB test was positive in 8.8% (n=5) of patients both prior to and at the sixth month of treatment. Coherence between two tests was poor or fair when compared with all possible TST cut-off values both prior to and at the sixth month of anti-TNF therapy. Conclusion: Our results show poor coherence between T-SPOT.TB and TST for all possible cut-off values of TST. Thus, using both tests would be beneficial in screening LTBI until further studies bring new evidence on the subject.